MicroRNA regulation of natural killer cells - Sullivan, Ryan; Leong, Jeff; Fehniger, Todd (Frontiers in Immunology, 2013)
Natural Killer (NK) cells are innate immune lymphocytes critical for host defense against viral infection and surveillance against malignant transformation. MicroRNAs (miRNAs) are a family of small, non-coding RNAs that regulate a wide variety of cellular processes. Recent advances have highlighted the importance of miRNA-mediated post-transcriptional regulation in NK cell development, maturation, and function. This review focuses on several facets of this regulatory mechanism in NK cells: 1) the expressed NK cell miRNA transcriptome; 2) the impact of total miRNA deficiency on NK cells; 3) the role of specific miRNAs regulating NK cell development, survival, and maturation; 4) the intrinsic role of miRNAs regulating NK cell function, including cytokine production, proliferation, and cytotoxicity; and 5) the role of NK cell miRNAs in disease. Currently our knowledge of how miRNAs regulate NK cell biology is limited, and thus we also explore key open questions in the field, as well as approaches and techniques to ascertain the role of individual miRNAs as important molecular regulators.